The Influence of Digital Marketing and Influencers on Repurchase Intention for Kahf Facial Cleanser through Customer Trust - Rahadean Makhdani Rahmatullah Mubarik; Hartoyo Hartoyo; Sufrin Hannan (Dinasti International Journal of Education Management and Social Science, 2025)
Growing awareness among Indonesian men of skin health and personal appearance has significantly increased demand for male skincare products, especially in the facial cleanser segment. Local brands such as Kahf continue to face strong competitive pressure fom international brands that dominate the market. This study examines the influence of digital marketing and influencers on repurchase intention for Kahf facial cleanser products, with customer trust as a mediating variable. Using SEM-PLS and data collected from 265 respondents in the Jabodetabek area. The findings show that social media marketing significantly affects customer trust but does not directly influence repurchase intention. Digital content marketing and influencer marketing significantly affect both customer trust and repurchase intention. Customer trust also shows a strong direct influence on repurchase intention. Indirect effects reveal that only the influencer shows a significant mediating effect through customer trust.